2020
DOI: 10.3389/fnins.2020.00659
|View full text |Cite
|
Sign up to set email alerts
|

Potent Natural Antioxidant Carveol Attenuates MCAO-Stress Induced Oxidative, Neurodegeneration by Regulating the Nrf-2 Pathway

Abstract: Ischemic stroke is a severe neurological disorder with a high prevalence rate in developed countries. It is characterized by permanent or transient cerebral ischemia and it activates syndrome of pathological events such as membrane depolarization, glutamate excitotoxicity, and intracellular calcium buildup. Carveol is widely employed as anti-inflammatory and antioxidant in traditional Chinese medicine. In the present study, the neuroprotective effects of post-treated carveol were demonstrated against transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 74 publications
2
32
0
Order By: Relevance
“…The clinical syndrome of a higher dose of APAP has long been established, and the potent natural antioxidant carveol attenuates APAP-induced detrimental outcomes in hepatic tissue; thus, this study further attested to our previously published data. We previously demonstrated that carveol treatment attenuated ischemic stroke-induced neurodegeneration, by positively affecting the Nrf2 pathway, thereby leading to a reduced infarction area ( Malik et al, 2020 ). We demonstrated here that carveol reversed the oxidative and inflammatory cascades of APAP, possibly by triggering the Nrf2-dependent antioxidative mechanism, which is cross-linked to the pro-survival pathways ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical syndrome of a higher dose of APAP has long been established, and the potent natural antioxidant carveol attenuates APAP-induced detrimental outcomes in hepatic tissue; thus, this study further attested to our previously published data. We previously demonstrated that carveol treatment attenuated ischemic stroke-induced neurodegeneration, by positively affecting the Nrf2 pathway, thereby leading to a reduced infarction area ( Malik et al, 2020 ). We demonstrated here that carveol reversed the oxidative and inflammatory cascades of APAP, possibly by triggering the Nrf2-dependent antioxidative mechanism, which is cross-linked to the pro-survival pathways ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, role of the JNK pathway in inflammatory cascades and cellular death has been strongly established ( Ali A et al, 2020 ), and ROS and inflammatory cytokines can trigger JNK activation ( Ali A et al, 2020 ; Ali T et al, 2020 ; Ling et al, 2020 ). Furthermore, the p-JNK pathway has been implicated in various animal models and human diseases ( Shah et al, 2018 ; Li and Liu, 2019 ; Ali A et al, 2020 ; Ling et al, 2020 ; Malik et al, 2020 ), and the downregulation or inhibition of this pathway has been found to contribute to the protective strategy ( Shah et al, 2019 ). We observed similar activities in the APAP-intoxicated group, and carveol significantly reduced p-JNK expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance was expressed in µmol GSH/g of the sample. To detect the GST activity, 42 a stock of 0.1 M potassium phosphate buffer was prepared using KHPO 4 and KH 2 PO 4 in a 1:2 ratio (pH 6.5). For the assay, 1 mM GST and 1 mM CDNB were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…At 24 h post-MCAO, the expression of antioxidants was induced, and Tau-Cl treatment during the acute phase (1 h post-MCAO) further enhanced this induction, possibly mitigating ischemic brain damage. However, contradictory results have been reported regarding the expression and activation of antioxidant enzymes in MCAO models, with some reporting increasing [ 61 , 62 ] and some decreasing expressions [ 63 , 64 ]. These contradictions might be caused by the experimental conditions, such as reperfusion time and brain region assayed.…”
Section: Discussionmentioning
confidence: 99%